THE ROLE AND FUNCTION OF THE STATE IN ADVANCING ISLAMIC ECONOMIC SYSTEM: A GLOBAL PERSPECTIVE - Moh. Fakhri Siddiqi; Sitti Aisyah; Silvia Nurul Rahma (Al-Qalam Institute, Probolinggo, East Java, Indonesia, 2025)
The state has a significant responsibility in creating prosperity and welfare for its people in accordance with sharia principles. This concept has been discussed by prominent thinkers such as Al-Ghazali and Al-Mawardi, who emphasized the importance of market supervision, fairness in resource distribution, and economic stability. This paper outlines the role of the state in managing economic factors such as allocation, distribution, and stabilization, as well as the state's essential role in addressing market failures and negative externalities. Furthermore, the discussion includes the relevance of Ibn Taimiyyah's thoughts to the modern economic system in Indonesia, including monetary policy strategies, infrastructure development, and equitable resource management. In conclusion, the role of the state is crucial in fostering public welfare and achieving the primary objectives of Islamic economics, namely falah and maslahah for all members of society